2013
DOI: 10.4236/wjnse.2013.33012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acidic and Polymeric Agents in Synthesis of TiO<sub>2</sub> Nanoparticles via a Modified Sol-Gel Method

Abstract: TiO 2 nano particles were synthesized in Rutile and Anatase phases by sol-gel method using two kind of complex agents, acidic (Citric Acid) and organic complex agent (acetyl acetone) at 400˚C, 500˚C, 650˚C sintering temperatures. The structural analysis by XRD diffraction confirmed phase formation of titanium oxide. Particles sizes were determined by using Scherrer formula. TEM was employed to confirm nano particles formation. The size of nano particles as well as Phase formation can be controlled by the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Moreover, synthesis by the sol-gel route using ethylene glycol as a gelling agent results in 19 nm-sized anatase [45]. Other organic gelation agents are ammonia [46] or citric acid and acetyl acetone as complex agents [47]. However, there is a variety of organic compounds used as solvents, surfactants, or additives in sol-gel methods to synthesize titania particles [48].…”
Section: Industrial Production Of Titania Polymorphsmentioning
confidence: 99%
“…Moreover, synthesis by the sol-gel route using ethylene glycol as a gelling agent results in 19 nm-sized anatase [45]. Other organic gelation agents are ammonia [46] or citric acid and acetyl acetone as complex agents [47]. However, there is a variety of organic compounds used as solvents, surfactants, or additives in sol-gel methods to synthesize titania particles [48].…”
Section: Industrial Production Of Titania Polymorphsmentioning
confidence: 99%
“…Therefore, the TiO 2 NP production method has become a crucial part of nanotechnology. Because TiO 2 nanocolloids produced using chemical methods contain elements other than titanium and oxygen due to the suspending agent added during the process [ 8 , 9 , 10 , 11 ], these TiO 2 nanocolloids can only be employed in certain fields. In addition, dust diffusion during the colloid production process is harmful to the human body and environment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DSC is based on a sensitized thin film of nanostructured, mesoporous TiO 2 , which is an attractive low-cost, nontoxic, wide band gap semiconductor, with excellent chemical stability and (photo)­catalytic activity, specifically as a nanostructured material. ,, A wide variety of synthesis methods have been developed to tune the crystal phase, nanoparticle size and morphology, and the resulting optical, physical, and chemical properties. ,, The three main crystal phases are anatase, rutile, and brookite; the first two phases have a tetragonal crystal structure, whereas brookite is orthorhombic. ,, TiO 2 -based DSCs are generally fabricated using pure anatase nanoparticulate films to achieve the highest efficiencies; however, other phases of TiO 2 may be equally attractive. , Several reports exist on the use of either rutile or brookite nanomaterials but generally the efficiency is found to be lower; however, especially brookite has shown promise exhibiting a larger open-circuit voltage than anatase-based solar cells. Although both materials are TiO 2 , significant differences may exist in several crucial parameters, including the energetic position of the conduction band, the distribution and density of trap states, electron mobility, and the rate constant for electron-transfer rate to the solution. , Both rutile and brookite are much more difficult to synthesize in nanoparticulate morphology related to a higher surface energy, and it is particularly complicated to obtain brookite nanomaterials of high purity. ,,,, Hence, most of the reports in the literature on the applications of brookite in DSC actually use brookite–anatase mixed materials, which complicates the analysis of the performance. In a recent paper, the synthesis of pure brookite nanomaterials has been described, and it is concluded that a combination of lower dye loading with lower collection efficiency results in a lower solar cell efficiency for the brookite-based cells, despite a higher open-circuit voltage .…”
Section: Introductionmentioning
confidence: 99%